The Impossibilities of the Circular Economy Separating Aspirations from Reality - Lehmann, Harry; Hinske, Christoph; de Margerie, Victoire; Slaveikova Nikolova, Aneta (Factor X: Studies in Sustainable Natural Resource Management, 2023)
The fifth Factor X publication from the Federal Environment Agency (Umweltbundesamt, UBA), The Impossibilities of the Circular Economy provides an overview of the limits to the circular economy, emphasising the relationship between integrated resource use and more systemic leadership-management approaches. On a European level, the book ties into the recent European Green Deal and aims to empower actors across sectors and EU member countries to transition from existing linear models of value capture and expression to more systemic-circular solutions of value capture and expression. The volume provides a hands-on contribution towards building the knowledge and skill sets of current and future decision-makers who face these complex-systemic crises in their day-to-day business. The book further provides access to best practices from cutting-edge research and development findings, which will empower decision-makers to develop a more sustainable and equitable economy. Providing solutions for a more sustainable economy, this book is essential reading for scholars and students of natural resource use, sustainable business, environmental economics and sustainable development, as well as decision-makers and experts from the fields of policy development, industry and civil society.